Strategi Manajemen Krisis Public Relations PT Blue Bird Group - Suryani, Ita; Sagiyanto, Asriyani (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2018)
ABSTRACTOne of the activities of Public Relations is to perfom a communication function in deveoping institutional communication with the public to realize goodwill and mutual understanding. In a crisis situation, Public Relations plays a vital role. The profession demands the ability to design, to protect, and to maintain the company's reputation in the public challenge. Blue Bird's commitment to change is one of the strategies of management crisis known as the